Tandem Structures Semiconductors Based on TiO2_SnO2 and ZnO_SnO2 for Photocatalytic Organic Pollutant Removal - Enesca, Alexandru; Isac, Luminita (Nanomaterials, 2021)
The photocatalyst materials correlation with the radiation scenario and pollutant molecules can have a significant influence on the overall photocatalytic efficiency. This work aims to outline the significance of optimizing the components mass ratio into a tandem structure in order to increase the photocatalytic activity toward pollutant removal. ZnO_SnO2 and TiO2_SnO2 tandem structures were obtained by the doctor blade technique using different mass ratios between the components. The samples contain metal oxides with crystalline structures and the morphology is influenced by the main component. The photocatalytic activity was tested using three radiation scenarios (UV, UV-Vis, and Vis) and two pollutant molecules (tartrazine and acetamiprid). The results indicate that the photocatalytic activity of the tandem structures is influenced by the radiation wavelength and pollutant molecule. The TiO2_SnO2 exhibit 90% photocatalytic efficiency under UV radiation in the presence of tartrazine, while ZnO_SnO2 exhibit 73% photocatalytic efficiency in the same experimental conditions. The kinetic evaluation indicate that ZnO_SnO2 (2:1) have a higher reaction rate comparing with TiO2_SnO2 (1:2) under UV radiation in the presence of acetamiprid.
Keywords: metal oxides; doctor blade; tandem structures; photocatalysis; kinetics